Cetaceans and cetacean research in the Indian ocean sanctuary - Leatherwood, Stephen; Donovan, Gregory P. (Nairobi, Kenya UNEP, 1991)
Marine Mammal Technical Report Number 3
Keywords: Cetacea--Research--Indian Ocean Sanctuary